THE INTIMACY TRIPLE BIND: STRUCTURAL INEQUALITIES AND RELATIONAL LABOUR IN THE INFLUENCER INDUSTRY - Glatt, Zoë (AoIR Selected Papers of Internet Research, 2023)
The careers of social media content creators, or influencers, live or die by their ability to cultivate and maintain an invested audience-community. To this end, they are encouraged to practise relational labour (Baym, 2018) to build authentic self-brands and intimacy with audiences. Drawing on a longitudinal ethnographic study of the London influencer industry (2017-2023), this paper examines relational labour through an intersectional feminist lens, foregrounding the ways in which structural inequalities shape relationships between creators and their audiences. This research found that the tolls of managing audience relationships are higher for marginalised creators—especially those who make critical leftist and feminist content—who find themselves on an uneven playing field in the challenges they face as well as the coping strategies at their disposal. Creators employed four key tactics to navigate relational labour and boundaries with audiences: (1) leaning into making rather than being content; (2) (dis)engagement with anti-fans through silence and digital self-harm; (3) retreating into private community spaces, away from the exposure of public platforms; and (4) turning off public comments. Marginalised creators find themselves in an intimacy triple bind, already at higher risk of trolling and harassment, yet under increased pressure to perform relational labour, adversely opening them up to further harms in the form of weaponised intimacy. Findings highlight the individualisation of risk and harm as a structural norm in the influencer industry, raising serious questions about the lack of accountability and responsibility that platforms show towards the creators who generate profit for them.